PRARANCANGAN PABRIK DIAMIL PHTHALAT DARI AMIL ALKOHOL PHTHALIC ANHIDRID DENGAN KAPASITAS 25.000 TON/ TAHUN - , THOMAS HERDIAN ABI PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Diamyl phthalate is an ester compound that is widely used in polymers industry as a platicizer especially on PVC synthesis.. Development opportunities of methyl benzoate industry in Indonesia is quite large, considering that there is no manufacturer listed has been established in Indonesia. The plant is planned to operate for 330 days / year with a diamyl phthalate production capacity of 25000 tons / year. The main raw material required is as much as 10470,3824 ton / year of 99% amyl alcohole and 13439,0467 tons / year of phtalic anhydride. The method used is the esterification with sulfuric acid catalyst. In general, diamyl phthalate manufacturing stages process is as follows: (i) reaction between amyl alcohole and phtalic anhydride with sulfuric acid catalyst in a continuous-stirred tank reactor, (ii) neutralization of acid catalyst using 40% NaOH solution, (iii) separation of salt neutralization results, (iv) diamyl phthalate product purification through flashing and distilation. As a support, utility plant unit supplies the cooling water as much as 376,8336 tons / hour, 1096,3747 kVA electricity, compressed air up to 100 m3/hr, and 3,8488 tons / hour steam. The plant will be established in the city of Gresik, East Java province, with consideration of raw material oriented. Gresik region close to the phtalic anhydride industry, and close to the harbor making it easier to procure raw materials amyl alcohole imported from China as well as the marketing of the product diamyl phthalate. Plant location close to the Brantas River, so that the source of water for utility plant unit derived from river water. Calculation of economic evaluation results is fixed capital required equal to $11,838,848.92 + Rp36.346.164.874,79 and working capital equal to $11,338,581.99 + Rp19.706.606.308,73. At 100% production rate, obtained ROI before tax of 18.89%, ROI after tax of 9.45 %. POT before tax of 3,46 years, POT after tax of 5.41 years, with BEP at 52.98%, SDP at 30,75%, and 19.25% for DCFRR. Based on consideration of the economic evaluation results, this diamyl phtalate plant with capacity 25000 tons / year worth to be studied further.